2022
DOI: 10.3390/ani12192572
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Diversity and Abundance of the Red Fox (Vulpes vulpes) Faecal Resistome and the Phenotypic Antibiotic Susceptibility of Indicator Bacteria

Abstract: The WHO considers that antimicrobial resistance (AMR) is among the ten greatest global public health risks of the 21st century. The expansion of human populations and anthropogenically related activities, accompanied by the fragmentation of natural habitats, has resulted in increased human–wildlife interaction. Natural ecosystems are therefore subjected to anthropogenic inputs, which affect the resistome of wild animals. Thus, urgent multisectoral action is needed to achieve the Sustainable Development Goals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
1
4
1
Order By: Relevance
“…The percentage of identified Enterococcus spp. isolates that were resistant to at least one antimicrobial agent was lower than 73% in Portugal [37] and Italy, where 35% of all isolates were susceptible to all the tested antimicrobial agents [38]. In the present study, no MDR isolates were found that resulted in a conflicting finding with those of previous authors, who reported the prevalence of MDR in Enterococcus from 3% in red foxes in Portugal [37] to 63% in wild Pampas foxes (Lycalopex gymnocercus) in Brazil [35].…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…The percentage of identified Enterococcus spp. isolates that were resistant to at least one antimicrobial agent was lower than 73% in Portugal [37] and Italy, where 35% of all isolates were susceptible to all the tested antimicrobial agents [38]. In the present study, no MDR isolates were found that resulted in a conflicting finding with those of previous authors, who reported the prevalence of MDR in Enterococcus from 3% in red foxes in Portugal [37] to 63% in wild Pampas foxes (Lycalopex gymnocercus) in Brazil [35].…”
Section: Discussioncontrasting
confidence: 92%
“…The identified high rates of antimicrobial resistance in Enterococcus spp. to tetracycline, erythromycin, and ciprofloxacin were in agreement with the findings of previous research on Carnivora [36][37][38]. Resistance to tetracyclines and ciprofloxacin in Enterococcus spp.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…During tetracycline treatment, there is a decrease in the abundance of susceptible bacteria, which can lead to an overgrowth of antibiotic-resistant bacteria [ 88 , 89 , 90 , 91 ]. This overgrowth can result in the development of antibiotic-associated diarrhea, which is a common side effect of tetracycline treatment.…”
Section: Tetracycline Effects On the Gut Microbiomementioning
confidence: 99%